Ceiling Effect in Cultivation : General TV Viewing, Genre-Specific Viewing, and Estimates of Health Concerns - Hetsroni, Amir (Journal of Media Psychology, 2014)
This study addressed two fundamental questions in cultivation: Is the total amount of time devoted to TV viewing a stronger predictor of cultivation than genre-specific exposure, and is the cultivation phenomenon in some domains capped by a ceiling effect? Data obtained from a content analysis of complete seasons of three successful medical programs – ER, House, and Grey’s Anatomy (66 episodes altogether) – were used to compose a survey which asked a representative sample of US adults (N = 281) to estimate the frequency of health concerns that were identified in the content analysis. The results partly support the cultivation hypothesis in its Gerbnerian version because the total amount of time devoted to TV viewing was found to be related to overestimating the proportion of dramatic diagnoses (poisoning and injuries) and exaggerating the mortality rate of inpatients; however, no effect was noted for items concerning elderly inpatients, and no effect was found for viewing of medical dramas. Since the distribution of the items concerning elderly inpatients was prone to a ceiling effect, the results lent support to the idea that the cultivation effect is sometimes capped by a ceiling effect.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTAyNy8xODY0LTExMDUvYTAwMDA5OQ